Secondary xylary features in proving truth/falsity of an alibi: examples of three important Indian commercial woods - More, Sandip; Paruya, Dipak Kumar; Bera, Subir (Current Botany, 2017)
Secondary xylary characters of wood are useful to identify a wood up to its generic or specific level and thus may prove or disprove the alibi of the retailers i.e., a wood is genuine or not. In the present study, 26 wood samples were collected from the local markets of Baruipur, Sealdah and Garia in Kolkata, West Bengal. Among them, 8 were sold as ‘Sandal wood’ (Santalum album), 4 as ‘Red Sanders’ (Pterocarpus santalinus) and 14 as ‘Sal wood’ (Shorea robusta). Results indicate that xylotomical features of most of the collected ‘sandal wood’ and ‘red sander’ samples did not match with the reference Santalum album and Pterocarpus santalinus samples whereas most of the collected ‘Sal wood’ samples from furniture shops matched with the reference samples of Shorea robusta. Present study successfully indicates that xylotomical investigations of commercial wood may establish the authenticity of wood of commerce.